Rising Adolescents Pregnancy Cases: An Additional Problem in Efforts to Reduce Maternal Mortality Rates - Adhi Pribadi (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
In the past three months, our institution have cared for 17 cases of pregnancies involving mothers under 20 years old. The youngest case involved a 14-year-old adolescent. These adolescent pregnancies are accompanied by various pregnancy pathologies, such as preterm birth, cephalopelvic disproportion, preeclampsia and eclampsia, mental disorders, and the potential for death for both the mother and the baby. In past decades, the majority of adolescent pregnancies were due to early marriage, while currently, unmarried pregnancies are on the rise. This is noteworthy, as it may be not only in Bandung and its surrounding areas but also throughout Indonesia and even globally. The increase in adolescent pregnancies results in the potential for maternal deaths, which are expected to increase in the future if this is not prevented and controlled properly.